Methane emissions from oil and gas production sites and their storage tanks in West Virginia. (December 2022) - Johnson, Derek; Clark, Nigel; Heltzel, Robert; Darzi, Mahdi; Footer, Tracey L.; Herndon, Scott; Thoma, Eben D.
Abstract: A measurement campaign characterized methane and other emissions from 15 natural gas production sites. Sites were surveyed using optical gas imaging (OGI) cameras to identify fugitive and vented emissions, with the methane mass emission rate quantified using a full flow sampler. We present storage tank emissions in context of all site emissions, followed by a detailed account of the former. In total, 224 well pad emission sources at 15 sites were quantified yielding a total emission rate of 57.5 ± 2.89 kg/hr for all sites. Site specific emissions ranged from 0.4 to 10.5 kg/hr with arithmetic and geometric means of 3.8 and 2.2 kg/hr, respectively. The two largest categories of emissions by mass were pneumatic devices (35 kg/hr or ∼61% of total) and tanks (14.3 kg/hr or ∼25% of total). Produced water and condensate tanks at all sites employed emissions control devices. Nevertheless, tanks may still lose gas via component leaks as observed in this study. The total number of tanks at all sites was 153. One site experienced a major malfunction and direct tank measurements were not conducted due to safety concerns and may have represented a super-emitter as found in other studies. The remaining sites had 143 tanks, which accounted for 42 emissions sources. Leaks on controlled tanks were associated with ERVs, PRVs, and thief hatches. Since measurements represented snapshots-in-time and could only be compared with modeled tank emission data, it was difficult to assess real capture efficiencies accurately. Our estimates suggest that capture efficiency ranged from 63 to 92% for controlled tanks. Highlights: Fifteen shale gas sites were surveyed with OGI and CH4 mass emissions quantified. Site specific CH4 emissions ranged from 0.4 to 10.5 kg/h. The largest CH4 emitter categories by mass were PCs followed by tanks. Tanks that deploy ECDS may still experience leaks that emit CH4 and other emissions. Connecting multiple tanks via a common header may obfuscate causes of emissions.